Utilization of Mn-Doped ZnSe/ZnS Core/Shell Quantum Dots for Rapid Detection of Escherichia coli O157:H7 and Methicillin-Resistant Staphylococcus aureus - Thi-Diem Bui; Quang-Liem Nguyen; Thi-Bich Luong; Van Thuan Le; Van-Dat Doan (Advances in Materials Science and Engineering)
In this study, Mn-doped ZnSe/ZnS core/shell quantum dots (CSQDs) were synthesized in aqueous solution using polyethylene glycol as a surface stabilizer and successfully applied in the detection of Escherichia coli O157:H7 and methicillin-resistant Staphylococcus aureus (MRSA) for the first time. The CSQDs were conjugated with anti-E. coli antibody and anti-MRSA antibody via protein A supported by 1-ethyl-3-(-3-dimethylaminopropyl)carbodiimide hydrochloride for fluorescent labeling of the intact bacterial cells. The detection was performed for the bacterial strains cultivated in Luria-Bertani liquid medium. The obtained results indicate that E. coli O157:H7 and MRSA can be detected within 30 min at a high sensitivity of 101 CFU/mL. This labeling method based on the highly fluorescent CSQDs may have great potential for use in the food industry to check and prevent outbreaks of foodborne illness.